(untitled) (EAAE Annual Conference Proceedings, 2023)
Traditional practices for training first-year students in architecture, tend to rely on hard-core skill training, digitalisation and programmatic exercises. However, these pragmatic methods have shown low impact on student’s creativity, experimental skills or spatial literacy.